Pengaruh stres kerja dan konflik kerja-keluarga terhadap counterproductive work behavior (CWB): Peran kepuasan kerja sebagai variabel intervening - Tyas, Purwaningrum; Nabila, Rifda (Nur Science Institute, 2023)
This research aims to determine the effect of work stress and work-family conflict on counterproductive work behaviour, with job satisfaction as an intervening variable. This research uses a quantitative type with a population of CV Tirta Makmur Ungaran employees. The sampling technique used in this research was a saturated sample with 100 respondents. The analytical method used in this research is path analysis. The results of statistical tests show that work stress and work-family conflict positively affect counterproductive work behaviour. Job stress affects job satisfaction negatively. Work-family conflict does not have a significant influence on job satisfaction. Job satisfaction hurts counterproductive work behaviour. Job satisfaction can mediate the relationship between work stress and counterproductive work behaviour, while work-family conflict does not.